Analisis Efektivitas Mesin Disch Caller Menggunakan Total Productivate Maintenance (TPM) Studi Kasus : PT. PM - Almaasah, Irfan Faalih Aziz; Khoiroh, Siti Muhimatul (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research aims to analyze the effectiveness of the Disch Caller machine at PT. PM by applying the Total Productive Maintenance (TPM) method. The method includes calculating the Overall Equipment Effectiveness (OEE) to measure machine performance and analyzing the Six Big Losses to identify productivity losses. The results show that the average OEE value of the Disch Caller machine is 69.15%, which is below the international standard of 85%. The analysis of Six Big Losses identified major losses, including reduce speed losses and equipment failure losses. These losses are caused by insufficient preventive maintenance, substandard material quality, and suboptimal working environment conditions. The proposed improvements include implementing a more disciplined preventive maintenance schedule, controlling material quality, and improving the working environment. Additionally, providing operator training and enhancing coordination between the maintenance team and operators are recommended to support machine effectiveness. Implementing these strategies is expected to increase the OEE value, reduce downtime, and enhance the production process at PT. PM. Keywords: Disch Caller, Overall Equipment Effectiveness, Productive Maintenance, Six Big Losses.